2013
DOI: 10.3389/fimmu.2013.00342
|View full text |Cite
|
Sign up to set email alerts
|

Association Analysis of IL10, TNF-α, and IL23R-IL12RB2 SNPs with Behçet’s Disease Risk in Western Algeria

Abstract: Objective: We have conducted the first study of the association of interleukin (IL)-10, tumor necrosis factor alpha (TNF-α), and IL23R-IL12RB2 region single nucleotide polymorphisms (SNPs) with Behçet’s disease (BD) in Western Algeria.Methods: A total of 51 BD patients and 96 unrelated controls from West region of Algeria were genotyped by direct sequencing for 11 SNPs including 2 SNPs from the IL10 promoter [c.-819T > C (rs1800871), c.-592A > C (rs1800872)], 6 SNPs from the TNF-α promoter [c.-1211T > C (rs179… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 66 publications
2
13
0
Order By: Relevance
“…A significant association (reaching a GWAS p value) of the IL-23R gene with BD was found at the SNP rs11209026 (Gly149Arg) in Japanese, and at the SNP rs76418789 (Arg381Gln) in Turkish cohort [61]. The association between BD and the IL-23R/IL-12RB2 genes appeared to be consistent in multiple reports with different populations including Turkey [52], Japanese [53], Han Chinese [62,63], Iranian [64], Western Algeria [65], and Korean [66].…”
Section: Il-12a Il-23r and Il-12rb2supporting
confidence: 80%
“…A significant association (reaching a GWAS p value) of the IL-23R gene with BD was found at the SNP rs11209026 (Gly149Arg) in Japanese, and at the SNP rs76418789 (Arg381Gln) in Turkish cohort [61]. The association between BD and the IL-23R/IL-12RB2 genes appeared to be consistent in multiple reports with different populations including Turkey [52], Japanese [53], Han Chinese [62,63], Iranian [64], Western Algeria [65], and Korean [66].…”
Section: Il-12a Il-23r and Il-12rb2supporting
confidence: 80%
“…However, BD is now regarded as one of the major autoinflammatory diseases . The genetic association of BD with human leucocyte antigen‐B51 explains only 20% of the disease heritability, and a polygenic origin of this disorder has been shown by genome‐wide association studies, revealing variants in the genes ERAP1 , IL10 , IL23R , CCR1 , STAT4 , KLRC4 and IL12A . The fact that BD is characterized by hyperactive neutrophils and recurrent episodes of neutrophilic inflammation, without a causative autoantigen or respective autoantibodies, opened up the possibility that BD may be an autoinflammatory disease and that IL‐1 may also be involved in its pathogenesis.…”
Section: Partially Interleukin‐1‐mediated Neutrophilic Dermatoses As mentioning
confidence: 99%
“…39,80,81 The genetic association of BD with human leucocyte antigen-B51 explains only 20% of the disease heritability, 82 and a polygenic origin of this disorder has been shown by genome-wide association studies, revealing variants in the genes ERAP1, IL10, IL23R, CCR1, STAT4, KLRC4 and IL12A. [83][84][85][86][87][88][89] The fact that BD is characterized by hyperactive neutrophils and recurrent episodes of neutrophilic inflammation, without a causative autoantigen or respective autoantibodies, opened up the possibility that BD may be an autoinflammatory disease and that IL-1 may also be involved in its pathogenesis. Indeed, elevated levels of IL-1b have been reported in BD, 90 and excellent clinical responses have been reported in BD and BD-associated uveitis with IL-1-targeted therapy.…”
Section: Sweet Syndrome (Acute Febrile Neutrophilic Dermatosis)mentioning
confidence: 99%
“…A report from Japan suggested that the IL23R gene was associated with autoimmune thyroid diseases (AITDs), but that this was restricted to a specific ethnic group 21. Previous studies have shown a stronger association of IL23R with Behcet’s disease in patients from Turkey22 as compared with cases from Algeria 23. Two SNPs located in the second haplotype block of the IL23R gene showed a marginal association with the risk of polyarticular psoriatic arthritis (p=0.05) in a Romanian case–control cohort 24.…”
Section: Discussionmentioning
confidence: 99%